Estimating the Oral Absorption from Self-Nanoemulsifying Drug Delivery Systems Using an In Vitro Lipolysis-Permeation Method - Mette Klitgaard; Anette Müllertz; Ragna Berthelsen (MDPI AG, 2021)
The aim of this study was to design an in vitro lipolysis-permeation method to estimate drug absorption following the oral administration of self-nanoemulsifying drug delivery systems (SNEDDSs). The method was evaluated by testing five oral formulations containing cinnarizine (four SNEDDSs and one aqueous suspension) from a previously published pharmacokinetic study in rats. In that study, the pharmacokinetic profiles of the five formulations did not correlate with the drug solubilization profiles obtained during in vitro intestinal lipolysis. Using the designed lipolysis-permeation method, in vitro lipolysis of the five formulations was followed by in vitro drug permeation in Franz diffusion cells equipped with PermeaPad® barriers. A linear in vivo-in vitro correlation was obtained when comparing the area under the in vitro drug permeation-time curve (AUC0-3h), to the AUC0-3h of the plasma concentration-time profile obtained from the in vivo study. Based on these results, the evaluated lipolysis-permeation method was found to be a promising tool for estimating the in vivo performance of SNEDDSs, but more studies are needed to evaluate the method further.